Government ideology and party priorities: the determinants of public spending changes in Italy. (21st March 2016) - Russo, Federico; Verzichelli, Luca
Abstract : The literature developed by scholars dealing with policy agendas suggests that it is more important to look at changes in governments' priorities rather than in their ideology, and criticizes the partisan theory as inadequate. However, hypotheses based on conventional wisdom and normative theories, holding that the identity of the governing parties matters for the allocation of public expenditures, are still recurrent in the debate. And many empirical studies found mixed evidence on the importance of party ideology. Focussing on Italy (1948–2009), this article empirically tests whether shifts in governments' ideology and policy priorities are related to public spending changes in four policy sectors. The results indicate that shifts in governments' priorities are related with public spending changes in welfare and defence, while they are not relevant to explain changes in public order and education spending. Government ideology is relevant only when it comes to defence spending, but this influence can be hindered by veto players. We argue that these findings do not disprove the importance of partisan politics but warn us against relying too much on the distinction between left and right parties. At the same time, more research is needed to understand under which conditions partisan preferences translate into changing public policies.